Some remarks on the rarefaction of the renewal processes - Mogyorödi, J. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ю. Модеруди. Несколько замечаний о разрежении рекуррентных потоков J. Moderudi. Kelios pastabos apie rekurentinių srautų išretinimą